[tex]\bf (\stackrel{x_1}{2}~,~\stackrel{y_1}{6})\qquad (\stackrel{x_2}{-2}~,~\stackrel{y_2}{-10}) \\\\\\ slope = m\implies \cfrac{\stackrel{rise}{ y_2- y_1}}{\stackrel{run}{ x_2- x_1}}\implies \cfrac{-10-6}{-2-2}\implies \cfrac{-16}{-4}\implies 4 \\\\\\ \begin{array}{|c|ll} \cline{1-1} \textit{point-slope form}\\ \cline{1-1} \\ y-y_1=m(x-x_1) \\\\ \cline{1-1} \end{array}\implies y-6=4(x-2) \\\\\\ y-6=4x-8\implies y=4x-2[/tex]
Answer:
y = 4x - 2.
Step-by-step explanation:
The slope is difference in y values / difference in x values
= (6 - -10) / (2 - -2)
= 16 / 4
= 4.
Using the point-slope form of a line
y - y1 = m(x - x1) where m = slope and (x1, y1) is a point on the line, we have:
y - 6 = 4(x - 2)
y = 4x - 8 + 6
y = 4x - 2.